Unseen Aspects Of Wound Healing: An Overview - SAHA RAJSEKHAR, (International Journal of Pharma and Bio Sciences, 2011)
Wound and its healing process are thought to be complicated process in the world. In fact, a wound heals in an orderly effective and in a systematic manner. The process of wound healing can be divided into four distinct phases but seen to be overlapping with each other. To distinguish the various phases of wound healing biological markers are used. Although the wound is accidental or surgical, it follows the basic healing procedure and the factors governing the healing of wound are also the same. This review describes the details regarding the wound and its types, phases of healing, biological process involved in normal and pathological wound healing. The feature of the review article is that we have touched the unseen aspects of nutrition support in wound healing. Nutritional deficiencies can impede wound healing, and several nutritional factors required for wound repair may improve healing time and wound outcome. To promote wound healing in the shortest time possible, with minimal pain, discomfort, and scarring to the patient, it is important to explore nutritional and botanical influences on wound outcome.